Pengaruh Lama Perendaman Benih Pepaya (Carica papaya L.) Dalam Ekstrak Bawang Merah (Allium ascolanicum L.) Terhadap Pertumbuhan Bibit - Soleha Soleha; Yustitia Akbar; Chika Sumbari (CULTIVATE: Journal of Agriculture Science, 2023)
Research in the form of a field experiment on "The Effect of Soaking Time of Papaya (Carica Papaya L.) Seeds in Shallot Extract (Allium ascolanicum L.) on Seedling Growth. It has been carried out in the form of a field experiment that has been carried out in the experimental field of the Faculty of Agriculture, University of Muhammadiyah West Sumatra, Tanjung Gadang Koto Nan Ampek Village, West Payakumbuh District, Payakumbuh City, with Inceptisol soil type, and has an altitude of ± 514 meters above sea level, this experiment was carried out in starting from June 2023 to July 2023. This experiment used a completely randomized design (CRD) with 5 treatments and 4 replications, in each treatment there were 4 plants and 2 were sample plants. Treatment of papaya seeds soaked in water for 1 hour, papaya seeds soaked in shallot extract for 2 hours, papaya seeds soaked in shallot extract for 3 hours, papaya seeds soaked in shallot extract for 4 hours, papaya seeds soaked in shallot extract for 5 hours. Observational data on papaya seedlings were averaged and statistically analyzed using the F test. Parameters observed in this study were field emergence (days), seedling height (cm), number of leaves (strands), leaf length (cm), width leaves (cm), stem diameter (cm), growing percentage (%). From the results of this experiment it can be concluded that due to long soaking of papaya seeds in shallot extract it has not been able to have a significant effect on the growth of papaya seedlings aged 45 HST.